(untitled) (Ágora Journal, 2024)
After the Law of November 7, 1831, prohibited entry of enslaved Africans into Brazil, illegal landings began to occur all along the coast, such was the case in Alagoas. This paper analyzes how these landings occurred from the 1831 until the end of the Regency period in 1840 and seek to understand the dynamics of the events that made these actions viable. It focuses on relations between the presidents of the province and local powers to better understand how the landings could be successfully carried out throughout the 1830s. In this way, it analyzes the regional context in a dialogue with the main political issues during the formation of the Brazilian State: the relation between the project of political centralization and the maintenance of the autonomy of local powers that be. The research is based on sources from different archival collections. Analyzing their modes of production and the various information withheld seek to contribute to knowledge of the illegal slave trade to Brazil in the XIX Century.